Republicanism Without Republic. Kant's Political Philosophy in its Historico-Systematic Context - Zöller, Günter (Studia Kantiana, 2023)
The essay assesses the character, extent and limits of Kant's republican commitments in political philosophy in a twofold perspective. Historically, Kant's recourse to republican political principles is placed in the context of the early modern discourse about forms of rule and types of government in general and about the relative merits of monarchical and republican constitutions in particular. Systematically, Kant's political republicanism is tied to his philosophy of law in general and to his account of public law in particular. Throughout the paper argues for a non-republican republicanism in Kant that imports basic features of modern republican theory and practice into a juridico-political context marked by enlightened monarchical absolutism and by an anti-revolutionary conception of political history. Section 1 opens with reflections on the timeliness and untimeliness of political philosophy and then sketches the career of republican thought in classical antiquity. Section 2 follows the trajectory of modern republican thought from Machiavelli to Montesquieu. Section 3 outlines the normative nature and the jural character of republicanism in Kant. Section 4 details the distinct political profile of republican rule in Kant.